A Systems Analysis of the Relationships Between Anemia and Ischemic Stroke Rehabilitation Based on RNA-Seq Data - Wang, Yingying; Huang, Xingxian; Liu, Jianfeng; Zhao, Xuefei; Yu, Haibo; Cai, Yunpeng (Frontiers in Genetics, 2019)
Ischemic stroke (IS) is one of the main causes of morbidity and disability worldwide due to its complex mechanism. Anemia was characterized as a risk factor of IS because the direct connection between central nervous system, blood supply, and tissue oxygen delivery. As the key oxygen-carrying molecule in the blood, hemoglobin (Hb) may be decisive for the destiny of penumbral area or influence the brain recovery and neurologic function, which could finally affect the outcome of IS. However, more detailed information on the expression levels of Hb related genes were still lacking possibly because the concentration of Hb was determined by the genes’ expression several hours ago which may make the researches more difficult to perform. This time gap between gene expressions and protein concentration could make these genes as predictive bio-markers for IS outcome. In this study, we choose 28 IS patients, of which 12 were suffering from anemia. Statistical analyses results showed that the outcome of the patients were different when dividing them into two groups characterized by Hb concentration. 2 sex and age matched patients were first chosen to perform RNA-seq analyses twice on different time points, after which the Hb counts were tested at least 24 hours after sequencing. Results showed that the outcome of anemia patients was poor compared with non-anemia patients. Two other patients were then chosen for analyses which excluded the coincidence of other factors. The results showed that the low value of Hb under 13 g/dL in men were closely related to the poor outcome of IS patients. Different expressed Hb related genes were tested and 6 genes were shown to be positively correlated with the recovery degree of IS patients: ELANE, FGF23, HBB, PIEZO1, RASA4, and PRTN3. Gene CPM was shown to be correlated with clinical outcome negatively. All of the 7 genes were validated to be related to stroke using real-time PCR or literature search. Taken together, these genes could be considered as new predictors for the recovery of IS patients.